Using non‐linear mixed effects models to identify patterns of chick growth in House Sparrows Passer domesticus. (23rd September 2015) - Aldredge, Robert A.
Abstract : For many animals, adult size is an important determinant of fitness. Thus, after a period of food restriction, offspring often grow quickly to approach an optimal size. Offspring can approach an optimal size by increasing mass faster than the peak growth of offspring that do not delay development (compensatory growth) or by extending the period of rapid growth to reach an optimal size (catch‐up growth). Unfortunately, the most common statistical techniques make it difficult to differentiate alternative growth patterns among developing offspring. Here, I show how random effect estimates can be used to uncover important variation in growth in a short‐lived passerine, the House Sparrow Passer domesticus . Specifically, I show that much of the variation in offspring growth can be explained by differences in the timing of peak growth and in final adult size, both within a single population and within treatments of an experimental manipulation. These results suggest that much of the variation in offspring growth may be explained by factors other than growth rate. I also show that offspring that delay development either maintain slow but steady growth across development and reach a small adult size, or extend the period of rapid growth to reach an optimal size, indicative of catch‐up growth. This pattern of extending the period of rapid growth may allow offspring to minimize the cellular damage caused by compensatory growth but still maximize size‐related fitness benefits (e.g. increased survival and fecundity) prior to fledging.